Subject-predicate agreement restrictions in Persian - Sedighi, Anousha (University of Ottawa (Canada), 2005)
This work investigates two distinct constructions which appear to induce a constraint on verbal agreement. The first construction involves inanimate plural subjects and verbs appearing in third person singular/default morphology. Adopting the framework of Distributed Morphology which has recently been used as a key to capturing several agreement restrictions in languages, I propose that the restriction caused by Animacy in Persian resides in post-syntactic morphology through an impoverishment operation. The second construction I study contains Psychological predicates which have not been entirely explored from the point of view of Psychological Constructions in the previous literature. The nominative experiencer does not induce agreement on the verb and the verb appears in third person singular, which provides evidence for separation of agreement and Nominative case assignment. I argue that the lack of verbal agreement in Persian Psychological constructions is only apparent and I provide evidence to show that they do not involve compound verbs. I propose that these constructions have a Tense requirement and involve applied arguments. The experiencer is licensed by a Super High Applicative head which takes a TP (a sentential predication/full proposition) as complement. Furthermore, I propose that the Super High Applicative phrase is a strong phase, a new category to be added to the set of strong phases proposed by Chomsky 1999-2004.
Keywords: Language, Linguistics.